Crystallographic Patterns in Turkish-Islamic Architecture with The Perspective of The History of Mathematics and Crystallography - Kökcü, Ayşe (Journal of History Culture and Art Research, 2021)
Our study is an introduction to the underlying reasons why the concept of crystal (crystallographic) pattern, which emerged from the union of mathematics and crystallography in the 20th century, is a frequently used ornamental element in Turkish-Islamic architectural works dating back about 9 centuries. Our aim is the geometric ornaments, which are generally handled by art historians; the aim is to underline that it is an area that needs attention for historians of mathematics, crystallography and architecture. We will try to reveal the emergence of crystal patterns, one of the patterns used by Turkish-Islamic architecture for centuries to cover many surfaces, in the fields of mathematics and crystallography, with the perspective of the history of science, in the context of two basic theories. The first of these theories is symmetry, and the second is group theory, which provides the basis for the mathematical explanation of symmetry. The examples of crystal structures, which are the subject of the science of crystallography, which developed with the help of new technologies discovered after the mathematical possibilities provided by symmetry and group theory, were applied centuries ago in Turkish-Islamic architecture will be emphasized. In this way, it will be noticed that the geometrical ornaments used in the artifacts from the Turks and the formation principles of the crystals are the same. These patterns, which were produced in a period when symmetry groups or crystallography were not known at all, were used as a kind of cultural element, especially by the Karakhanids, Seljuks, Anatolian Seljuks…etc. It is surprising that it is seen in all geographies that Muslim Turks have reached. Considering the history of mathematics and crystallography, it is understood that the crystal patterns used in architecture are a manifestation of the knowledge of Turkish-Islamic civilization in many sciences, especially geometry.